PENGARUH PENERAPAN INKUIRI TERBIMBING TERHADAP HASIL BELAJAR GAYA DAN HUKUM NEWTON DI MTS PONTIANAK - Fransiska Desi Susiati; Edy Tandililing; Erwina Oktavianty (Universitas Tanjungpura, 2020)
AbstractThis study aims to analyze the effect of the application of guided inquiry learning models on the learning outcomes of students on Newton's style and law material in class VIII Pontianak Islamic MTs. The form of this research is Quasi Experimental Design with Non equivalent Control Group Design. The sampling technique used is intact group. The instrument used in the form of a description test is 5 questions. Data were analyzed using Mann Whitney U test with α 5%. Obtained Zhitung <Ztabel (-2,566 <-1,96). Which means that H0 is rejected and Ha is accepted. This shows that there are differences in learning outcomes of students who are given inquiry-guided learning models with conventional learning. The effective of learning using guided inquiry learning models referred to in the high category with an effect size value of 0.8 and contributes 28.81% to the increase in learning outcomes of students.Keywords: guided inquiry, learning outcomes, newton style and law